Metadiscursive Boosting in Russian Courtroom Discourse: Enhancing Persuasiveness in Defense Speeches - O. A. Boginskaya (Дискурс профессиональной коммуникации, 2024)
Recent studies are revealing new aspects of courtroom discourse, examining its generation and applying novel analytical methods. Yet, despite their significance and complexity, the use of metadiscursive tools remains scarce. These tools offer substantial promise for analyzing discursive practices, increasingly seen as not just informative but also interactive and impactful. The inherently interactive and persuasive nature of courtroom discourse underscores the need for metadiscourse as a potent analytical instrument. Such an instrument encompasses mechanisms for expressing attitudes toward the propositional content and for drawing the recipient into a dialogue with the speaker. This article addresses the metadiscursive dimension of defense speeches as a distinct genre within courtroom discourse. The study uses quantitative analysis on a corpus of Russian-language courtroom texts, innovatively applying metadiscursive analysis to identify linguistic elements that enhance the persuasiveness of defense speeches, with a focus on the technique of boosting. Throughout the study, five types of boosters were identified – markers of certainty, evidentiality, intensity, solidarity, and superiority – each serving one of five pragmatic functions: to show the speaker’s confidence in the truth of their assertions, to point to the credibility and reliability of the source, to amplify the emotional impact of the statement, to denote the upper bounds of a continuum, and to reference commonly known facts or shared experiences of events or situations. The study reveals that boosting at the lexical level is predominantly achieved through the use of evidential verbs and nouns, adverbs of measure, degree, and time, as well as superlative adjectives. Additionally, the frequent use of first-person plural pronouns was observed. The findings suggest that adept use of boosters in courtroom discourse is indicative of a lawyer’s pragmatic competence and is crucial for effective communication with the court and the jury.